2020
DOI: 10.3389/fpsyt.2020.00038
|View full text |Cite
|
Sign up to set email alerts
|

Association Between BDNF Gene Variant Rs6265 and the Severity of Depression in Antidepressant Treatment-Free Depressed Patients

Abstract: Background: Brain-derived neurotrophic factor (BDNF) plays an important role in neuronal plasticity, and its dysregulation has been associated with the pathogenesis of mood and anxiety disorders. Prolactin (PRL) is a pituitary hormone which is also produced as a cytokine by immune cells and could be a neurotrophic factor regulating the functional activity of stress-related mechanisms. Aim: To investigate the possible relationship between depressive state and BDNF and PRL genotypes or levels with special refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 34 publications
0
21
1
Order By: Relevance
“…Conversely, a recently published case-control study has demonstrated positive relationships between T allele and the risk of major depression (Aldoghachi et al 2019). In the other study, T allele was associated only with the severity of depression (Losenkov et al 2020). Although an animal study identified a relationship between MetMet genotype and increased risk of anxietyrelated behavior, we found no impact of rs6265 on ANXD susceptibility.…”
Section: Discussioncontrasting
confidence: 89%
“…Conversely, a recently published case-control study has demonstrated positive relationships between T allele and the risk of major depression (Aldoghachi et al 2019). In the other study, T allele was associated only with the severity of depression (Losenkov et al 2020). Although an animal study identified a relationship between MetMet genotype and increased risk of anxietyrelated behavior, we found no impact of rs6265 on ANXD susceptibility.…”
Section: Discussioncontrasting
confidence: 89%
“…Losenkov and colleagues found an association between BDNF rs6265 and the 17item Hamilton depression rating scale (p=0.014) but not between BDNF rs6265 and the BDNF level. In the same study, the BDNF level was not reported to be associated with depression, indicating that BDNF rs6265 may only be involved in the severity of the disorder (Losenkov et al, 2020). Similarly, no significant difference was observed in the BDNF levels of 61 medicated depression patients and 50 controls (p=0.81), even following a course of electroconvulsive therapy.…”
Section: The Effects Of Bdnf Rs6265 On Neuropsychiatric Disorders 21mentioning
confidence: 87%
“…Also, the data has shown that there is a reduction of BDNF in the prefrontal cortex, amygdala and hippocampus of patients with this patology [7,73,74] as well as in postmortem brain of victims of suicide and depression [9]. In addition, it has been observed that stress, one of the main triggers of mood disorders such as anxiety and depression [75,76] induces a decrease in BDNF [10,77]. In line with these data, exposure to stress factors, which is one of the most used approaches to model depression in experimental animals, promoted a decrease in the levels of BDNF and TrkB expression in the hippocampus, cortex and amygdala of animal models of stress such as social defeat, containment stress (immobilization) and maternal deprivation [75,[78][79][80].…”
Section: Brain-derived Neurotrophic Factor and Major Depressive Disordermentioning
confidence: 98%